Elevation of the Chaunsath Yogini Temple - Temples of India Project Team (Jio Institute, 2024)
A view of the elevation of the Chaunsath Yogini Temple from the north showcases the lost mandapa portion connected to the mulaprasada. The common jagati (plinth or raised platform) of the temple partially survives.